Highlighting the difference in nanostructure between domain-forming and domainless protic ionic liquids. Issue 35 (2nd September 2022) - Sedov, Igor A.; Magsumov, Timur I.
Abstract : Nanoheterogeneity in some ionic liquids is a known phenomenon, but quantifying or sometimes even identifying it is not a straightforward task. Abstract : Nanoheterogeneity in some ionic liquids is a known phenomenon, but quantifying or sometimes even identifying it is not a straightforward task. We compared several known and suggested some novel approaches to identify and characterize domain segregation using the results of atomistic simulations. 10 ammonium-based protic ionic liquids with different propensity to form segregated polar and apolar domains as suggested by experimental studies were considered. They include butyl-, propyl-, 2-methoxyethylammonium nitrate, butyl- and propylammonium hydrogen sulfate, butylammonium thiocyanate (domain-forming liquids), ethylammonium and pyrrolidinium nitrate (weakly pronounced segregation), methylammonium and 2-hydroxyethylammonium nitrate (domainless liquids). Molecular dynamics simulations were performed using models based on the OPLS-AA force field with scaled ion charges. Results show that domains can be recognized and the characteristic domain length scale can be determined from peaks of Ripley's functions, peaks and large-period oscillations of finite-volume radial distribution function integral, or difference of such integrals for polar and apolar atoms, and peaks of local atom density variance. These peaks disappear with increasing temperature due to the disruption of segregated domains. In domain-forming liquids, apolar atoms are more homogeneously distributed in space than polar atoms. In addition, the probability of molecular-sized cavity formation is significantly higher in apolar domains, which determines better solubility of apolar species in domain-forming ILs. The suggested approaches can be applied to various nanostructured liquids including both ionic and molecular solvents and mixtures, as well as other systems with mesoscale ordering.